Real-World Effectiveness of 5-Aminolevulinic Acid Photodynamic Therapy for HPV-Related Lower Genital Tract Lesions: A Single-Center Retrospective Cohort Study (2021–2024) - Zhengzheng Chen; Hui Hong; Xiaoli Wang; Xiuyun Zhang (Discovery Medicine, 2026)
Background: Excisional procedures for high-risk human papillomavirus (HPV)-related lower genital tract lesions fail to eliminate the underlying HPV infection and carry fertility-related risks, leaving patients with persistent low- or high-grade lesions without an effective tissue-preserving option. Real-world data on 5-aminolevulinic acid photodynamic therapy (ALA-PDT) across the full lesion spectrum remain limited. This study evaluated composite and histological/cytological complete response rates of ALA-PDT and explored whether morphological and virological responses follow distinct temporal trajectories.Methods: In this single-center retrospective cohort study conducted between 2021 and 2024, 176 patients were included after excluding isolated vulvar intraepithelial neoplasia (VIN), isolated condylomata acuminata, and HPV infection <12 months without morphological lesions. A total of 177 treatment episodes were recorded, as one patient received two independent ALA-PDT courses separated by >6 months, and only the first episode was retained in the primary per-patient analysis. Of these, 174 patients had confirmed cervical or vaginal intraepithelial neoplasia (with or without concurrent vulvar lesions or condylomata acuminata), and 2 had persistent HPV infection without morphological lesions. All patients received standardized ALA-PDT (20% ALA; 635 nm; 120 J/cm2; 3–6 sessions). Of 174 patients with morphological disease, 147 had valid follow-up and constituted the primary efficacy population. The primary endpoint was composite complete response (CR), requiring concurrent morphological resolution, cytological normalization, and HPV clearance. A predefined secondary endpoint, histological/cytological CR (hCR), required morphological and cytological normalization irrespective of HPV status.Results: Among 147 evaluable patients with morphological disease, composite CR was 68.7% (101/147), with hCR of 83.0% (122/147) and overall response rate of 93.2% (137/147). These estimates were robust across follow-up strata (CR ≥6 months: 70.8%; ≥9 months: 73.3%) and after inverse probability weighting (68.1%). CIN 2/3 achieved the highest composite CR (85.7%). Cross-sectional observations suggested that cytological normalization may plateau earlier than HPV clearance, which continued to increase through 12 months.Conclusions: ALA-PDT demonstrated high efficacy across HPV-related lower genital tract lesions, with morphological response rates suggesting clinically meaningful disease control. These findings support ALA-PDT as an effective, tissue-preserving option for HPV-related lower genital tract lesions. Direct assessment of reproductive outcomes, sexual function, quality of life, and patient satisfaction was not feasible in this retrospective dataset and warrants future prospective studies.